IMPROVING THE STUDENTS’ VOCABULARY MASTERY THROUGH THE USE OF KIM (KEYWORD, INFORMATION, AND MEMORY CLUE) STRATEGY AT THE EIGHT GRADE STUDENTS OF SMP DWIJENDRA DENPASAR IN THE ACADEMIC YEAR 2019/2020 - Benedikta Onsimarta Jeharu; I Gusti Ayu Indah Triana Juliari (Widyasrama, 2020)
This study aims to improve the vocabulary of VIII-G class students of SMP Dwijendra Denpasar through the use of KIM strategy in the academic year 2019/2020. This research was a classroom action research. This research used two cycles, where each cycle consists of four stages, namely planning, implementing, observing, and reflecting. The subjects of this study was the students of VIII G class SMP Dwijendra Denpasar. The instruments used in this research were tests, observation sheet, interview guide, and lesson plans. In collecting the data, the researcher used observation and interview methods. The result of this research showed that there was an improvement in the students’ vocabularies. It could be seen from the students’ pre – test and post – test scores. The mean score of the students pre – test in this research was 54.5, while the mean score of post - test 1 was 73.7 and it was improve in the post-test II became 85. The students’ observation result by using KIM strategy was very satisfied because the students could follow each instruction that was given by the teacher. The result of interviewing the students showed that they could motivated and improved their vocabularies’ in English subject by using KIM strategy. It could be concluded that the use of KIM strategy could improve the students’ vocabularies.